Privatization in Transition Countries : A Sampling of the Literature - Havrylyshyn, Oleh.; McGettigan, Donal (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews a selection of studies on privatization experiences in transition countries. Empirical studies almost invariably show privatized enterprises outperform state enterprises. Moreover, the literature identifies de novo firms as being clearly the best performers, followed by outsider-dominated firms, while insider-dominated firms are the least efficient among those newly privatized. The importance of de novo firms in enlarging the private sector in transition economies is reviewed, along with the question of whether privatization efforts support or hinder de novo private sector development. Finally, the paper discusses the importance of providing a suitable market environment for successful private-sector development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet